2014
DOI: 10.4172/2157-7110.1000310
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Lactic Acid Bacteria for Antifungal Activity against Fungi

Abstract: Many chemical preservatives that target fungi growth in food have been approved and used for many years. Recently the consumers are looking and demanding for products without chemical preservatives and still maintain good shelf life and safe. The growth of spoilage fungi have been a global concern because of the economy loses and the health hazard of the mycotoxins produced by the spoilage fungi. A total of 22 lactic acid bacteria isolated from Tarhana and Lactic acid bacteria were screened for antifungal acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…LAB have been widely and safely used in the food and feed industries as probiotics or starters during the past decades (Franz et al 2010;Oliveira et al 2014). Recently, some studies reported the antifungal activities of these bacteria against some plant pathogenic fungi (Gajbhiye & Kapadnis 2016;Gupta & Srivastava 2014;Kharazian et al 2017;Kıvanc et al 2014;Oliveira et al 2014;Tropcheva et al 2014;Varsha et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…LAB have been widely and safely used in the food and feed industries as probiotics or starters during the past decades (Franz et al 2010;Oliveira et al 2014). Recently, some studies reported the antifungal activities of these bacteria against some plant pathogenic fungi (Gajbhiye & Kapadnis 2016;Gupta & Srivastava 2014;Kharazian et al 2017;Kıvanc et al 2014;Oliveira et al 2014;Tropcheva et al 2014;Varsha et al 2014).…”
Section: Introductionmentioning
confidence: 99%